L’animal éducateur ? De la spéci-ficité de l’animal homme dans les écrits de Nietzsche - Julie Dumonteil (Recherches Germaniques)
Nietzschean reflections on the nature of animal being are part of the philosophical anthropology, which inquires the human nature and its relationship to animals. The Darwinian evolution theory and life philosophy question the Aristotelian definition of the essence of a human being as an animal rationale. Nietzsche differentiates the Human Being from the other animals essentially through his failures. This study must therefore analyze how denatured and troubled the Human Being, in his nature and his path, is. This will lead us to consider the potential role of educator played by animal being to help human being forget about their speci-ficity to eventually enjoy life to the fullest.